Antibacterial adhesive injectable hydrogels with rapid self-healing, extensibility and compressibility as wound dressing for joints skin wound healing - Qu, Jin; Zhao, Xin; Liang, Yongping; Zhang, Tianlong; Ma, Peter X.; Guo, Baolin (Biomaterials, 2018)
Designing wound dressing materials with outstanding therapeutic effects, self-healing, adhesiveness and suitable mechanical property has great practical significance in healthcare, especially for joints skin wound healing. Here, we designed a kind of self-healing injectable micelle/hydrogel composites with multi-functions as wound dressing for joint skin damage. By combining the dynamic Schiff base and copolymer micelle cross-linking in one system, a series of hydrogels were prepared by mixing quaternized chitosan (QCS) and benzaldehyde-terminated Pluronic®F127 (PF127-CHO) under physiological conditions. The inherent antibacterial property, pH-dependent biodegradation and release behavior were investigated to confirm multi-functions of wound dressing. The hydrogel dressings showed suitable stretchable and compressive property, comparable modulus with human skin, good adhesiveness and fast self-healing ability to bear deformation. The hydrogels exhibited efficient hemostatic performance and biocompatibility. Moreover, the curcumin loaded hydrogel showed good antioxidant ability and pH responsive release profiles. In vivo experiments indicated that curcumin loaded hydrogels significantly accelerated wound healing rate with higher granulation tissue thickness and collagen disposition and upregulated vascular endothelial growth factor (VEGF) in a full-thickness skin defect model. Taken together, the antibacterial adhesive hydrogels with self-healing and good mechanical property offer significant promise as dressing materials for joints skin wound healing.